Developing creative team games players: From jazz to sport coaching - Santos, M.; Morgan, K. (International Journal of Sports Science & Coaching, 2019)
Traditional coaching methods position coaches at the centre of the learning process and do not encourage players to think creatively. This study challenged this assertion, through the application of pedagogical principles reported in jazz-related literature, which argue that creativity is best developed through collaboration. As such, the study aimed to develop players` creativity, through the application of pedagogical principles reported in jazz-related literature. An action research design was implemented, during a 14-weeks period, with a youth volleyball squad. Results demonstrated an impact upon match play; players showed their enhanced appreciation of the game`s complexity, by experimenting, collaborating, and generating creative solutions to challenges emerging within matches. In addition, the implementation of collaborative practices positively impacted upon the players` communication habits, which were both more frequent and effective. Although players demonstrated a similar modus operandi to jazz musicians, this study represents the first step in what coaches can learn from jazz creativity, and therefore further research is required to corroborate or challenge the results attained.